Development of a Simulation Model in FlexSim as a Support Tool for Curriculum Design - López Osorto, Gerson Fernando; Fuentes Mayen, Viviana Isabel; Abarca Montoya, Ismael Alfonso; Nelson Padilla, Mendel Ivan (LACCEI, 2025)
This research developed a simulation model using FlexSim to represent the academic progression of Civil Engineering students at UNITEC Tegucigalpa, based on the 2015 curriculum. The primary goal was to evaluate the technical feasibility of simulating a curriculum structure through discrete-event modeling, allowing for the early identification of academic bottlenecks before implementing new programs or reforms. The study followed three main phases: data collection and refinement, model construction, and statistical validation. Students were segmented by academic performance, enabling a differentiated simulation approach according to academic profiles. The resulting model represented idealized academic paths, assigning approval or failure probabilities per subject. However, because FlexSim is primarily designed for industrial systems, significant customization was required. As a result, the model became highly complex, not scalable to other programs, and difficult to replicate across different contexts. Despite these limitations, the simulation helped identify critical courses, particularly in the mathematics track, and led to the creation of a methodological guide to support similar future studies. While the model itself is not universally transferable, the underlying logic, segmentation approach, and technical insights offer a solid foundation for developing more flexible and scalable academic simulations in platforms better suited to educational environments.